Tradisi Tammu Taung Gaukang Karaeng Galesong dalam Masyarakat Makassar di Takalar (Analisis Semiotika Charles Sanders Pierce) - Citrawati, Nur; M., Asia; Fitri, Sakinah (Indonesian Journal of Social and Educational Studies, 2023)
Abstract.This study aims to describe the icons, indexes, and symbols in the equipment used in the traditional rituals of Tammu Taung Gaukang Karaeng Galesong using Charles Sanders Pierce's semiotic theory to analyze.  This type of research is field research (Field Research) and is qualitative. The methods used in collecting this research data are observation, interviews, and documentation. The results of the analysis in this study showed icons of (1) native chickens, (2) rakik-rakik, (3) songkolok, (4) tumpi-tumpi, (5) curves of kalomping. Index (1) White Glass, (2) drum/drum sound, (3) offering, (4) pakrappo, (5) paddupang. Symbols (1) rice, (2) coconut (3) banana leaves (4) white cloth, (5) candles, (6) brown sugar, (7) bananas, (8) buffalo, (9)  traditional clothing, (10) kaddo minnyak, (11) brown rice and  white rice , (12 ) black songkolok and white songkolok, (13) pababbasak (14) areca nut, (15) betel, (16) roast chicken (17) egg, (18)  pallubasa chicken and fried chicken,  (19) satay, (20) grilled fish  and  fried fish, (21) umba-umba, (22) rarongke , (23)  Layer cake, (24) Kanrejawa Picuru (25) Tuak (26) coconut water.  In general, the marks in the equipment used in the traditional rituals of Tammu Taung Gaukang Karaeng Galesong in Makassar society symbolize hope and prayer that Always get protection and prosperity of life as well as a form of respect.Keywords: Tradition, Makassar Society, Tammu Taung Gaukang Karaeng Galesong, Charles Sanders Pierce Semiotics.